SISTEM INFORMASI PERSEDIAAN BARANG PADA ATHLETIC MUSIC & SPORTS - Giann Moses Lase; Emma Rosinta Simarmata; Duma Megaria Elisabeth (Universitas Methodist Indonesia, 2021)
Athletic Music & Sports is a sales company located in Medan, North Sumatra. Athletic Music & Sports sells a variety of Music & Sports equipment. Therefore, Athletic Music & Sports has some data that requires computerized data management so that the resulting information system can be maximized. One of the things that requires computerized data management is inventory data management, where inventory data is one of the most important assets in every company. The management of computerized inventory data must also be accompanied by better security so that the security of the data is guaranteed. The system to be built is an inventory information system using visual basic and Microsoft Access as a database. The research methods used are case studies, observation, interviews, and library methods. This system is expected to be able to help Athletic Music & Sports to make the inventory system better and more structured.